Evaluation of the Relationship between Nutritional Habits, Seasonality Score and Eating Attitudes among University Students - Özekinci, Ayden; Türker, Perim Fatma; Köse, Beril; Yeşil, Esen (Progress in Nutrition, 2025)
Background and Aim: Seasonal changes influence individuals’ emotional states and physiological behaviors, including eating patterns. These shifts may be particularly pronounced among university students, who are undergoing developmental and lifestyle transitions. This study aimed to evaluate the relationship between seasonality, nutritional habits, and eating attitudes in university students. Methods: A cross-sectional study was conducted among 284 university students aged 19–25 years. The Seasonal Pattern Assessment Questionnaire (SPAQ) was utilized to assess the influence of seasonal variations on affect and behavior, while the Eating Attitudes Test-26 (EAT-26) was administered to screen for disordered eating behaviors and attitudes. Anthropometric measurements and self-reported nutritional behaviors were also collected. Results: The mean seasonality score (SS) was 12.24±4.66, and the mean EAT-26 score was 12.00±9.97. A statistically significant association was observed between higher seasonality scores and the presence of disordered eating attitudes (EAT-26 ≥20) (p<0.05). However, no significant correlations were found between seasonality or EAT-26 scores and anthropometric measurements. Additionally, most self-reported nutritional habits did not significantly differ based on seasonality or eating attitude scores, except that individuals who reported dieting had significantly higher EAT-26 scores (p<0.05). Conclusions: Seasonal affective changes appear to influence eating attitudes among university students. Given that disordered eating behaviors are more common in individuals with higher seasonality scores, it is crucial to raise awareness and implement preventive strategies. Future research should examine these relationships longitudinally across different seasons and populations.